THE CONCEPT OF HOSPITALITY MARKETING AND ITS SIGNIFICANCE TO THE SIERRA LEONE TOURISM INDUSTRY - Bangura, Aminata; Sesay, Adikali Kaba (International Journal For Research In Business, Management And Accounting, 2019)
The concept of hospitality marketing and its significance to the Sierra Leone tourism industry is a most needed education within the hospitality industry in Sierra Leone. The hospitality industry consists of businesses and institutions involving food and beverage, tourism and all kinds of lodging establishments. The friendly reception and treatment of guests is the responsibility of the people who work in the hospitality industry. The focus of this research is to enlighten the greater number of those who are in this industry. The study brings out the concept of hospitality and discusses the categories and demands of the market. How the industry should be managed is also factored in research. Guidelines on the macro and micro environment were brought out and discussed in detail. The findings and concepts would be used by industries to focus on ensuring employees and clients are aware of what hospitability management means and the other demands.